Nalidixic Acid Susceptibility Test for Screening Salmonella Isolates of Reduced Susceptibility/Higher Minimum Inhibitory Concentration to Ciprofloxacin - Agrawal, P.; Tuladhar, R.; Dahal, N. (Nepal Journal of Science and Technology, 2015)
Enteric fever is the major diagnosis among febrile patients in Nepal with yearly increase in nalidixic acid resistance and reduced ciprofloxacin susceptibility among Salmonella isolates. This study was carried out to evaluate the validity of nalidixic acid resistance as an indicator of reduced susceptibility of Salmonella isolates to ciprofloxacin. In this study, 999 blood specimens collected from suspected enteric fever patients visiting B&B Hospital were processed by standard microbiological techniques. Isolates were identified by biochemical tests and serotyping. Antibiotic susceptibility test was performed by Kirby Bauer disc diffusion method and CLSI recommended interpretive criteria. MIC of ciprofloxacin was determined by agar dilution method. Isolation rate of Salmonella species was 6.21%. Among 62 Salmonella isolates, 51 were S. typhi, 10 were S. paratyphi A and one isolate was S. paratyphi B. Only one isolate of S. typhi was multi-drug resistant. Resistance to ceftriaxone, cefixime and azithromycin was nil. On disc diffusion test, 55 isolates were resistant to nalidixic acid. Fifty-seven isolates were found to have increased (>0.125mg/ml) MIC of ciprofloxacin with the clinical and laboratory standards institute breakpoints. Nalidixic acid resistance showed a predictive value of 100% for ciprofloxacin resistance. Screening with nalidixic acid disc had a sensitivity of 100% and a specificity of 71.43% for the determination of decreased ciprofloxacin susceptibility. Before using ciprofloxacin for the treatment of enteric fever, appropriate identification of Salmonella isolates with reduced ciprofloxacin susceptibility is essential to limit the possible treatment failure and further development of highly resistant strains. DOI: http://dx.doi.org/njst.v15i2.12122 Nepal Journal of Science and Technology Vol. 15, No.2 (2014) 97-104